Estudos do Vídeo Musical - Branco, Sérgio Dias (2014)
Recensão a “The Music Video Reader” editado por Simon Frith, Andrew Goodwin, e Lawrence Grossberg, “Rocking Around the Clock: Music Television, Postmodernism, & Consumer Culture” de E. Ann Kaplan, “Le clip: histoire et esthétique” de Laurent Jullier e Julien Péquignot, e “Experiencing Music Video: Aesthetics and Cultural Context” de Carol Vernallis.